CORRELATION BETWEEN PARENTAL SOCIOECONOMIC STATUS AND STUDENTS’ ENGLISH ACHIEVEMENT - Henny Yulia (State Islamic University of Raden Fatah Palembang, South Sumatra, Indonesia, 2017)
The main purpose of this research was to find out if there was indeed a correlation between parental socioeconomic status and student’s achievement in English at the eleventh grade students of SMA N 1 OKU. Next problem of this research concerned with the dominat indicator of parental socioeconomic status, student’s achievement in English and correlation between parental socioeconomic status and student’s achievement in English. This research used correlation method.The population of the research was the eleventh grade students of SMA N 1 OKU, consisted 435 students. The sample was 111 students that were taken by using purposive sampling of eleventh grade students’ at SMA N 1 OKU in academic 2017/2018. The instruments used were questionnaire of parental socioeconomic status and the score of students’ English report. Based on the data analysis and the result of investigation the dominant indicator that influenced parental socioeconomic status was parent’s income with the percentage 59, 90%. Meanwhile, base on the students score there were no students in low level category, there were 25 students or 22, 52% got execelent category and there were 86 students or 77,47% got good category. It could be concluded that the students whose score were in good category came from good socioeconomic level. The coefficient of the correlation between parental socioeconomic status and students English achievement was 0,550.it mean that null hypothesis (Ho) was rejected and consequently the alternative hypothesis (Ha) was accepted. Therefore, the research concluded that the dominant indicator that influenced parental socioeconomic status was parents’s income. Next the most of students’ English achievement were included in good category. Therefore there was positive correlation between parental socioeconomic status and student’s achievement in English at the eleventh grade students’ of SMA Negeri 1 OKU.